Designing a general employee management model with an emphasis on performance management - Maryam Nasiri; Ameneh Firozabadi; Sanjar Slajagheh; Mahdi Mohamad Bagheri (مدیریت و چشم انداز آموزش)
Abstract The purpose of this research is to design a general management model of employees with an emphasis on performance management. The current research is applicable in terms of purpose, mixed in terms of implementation (qualitative-quantitative), and descriptive-survey in terms of nature. The participants in the qualitative part include 13 professors and experts in educational management and education managers, sampling by a targeted method, and the statistical population in the quantitative part includes 300 people from all the education and training staff of district one of Kerman, 187 of whom were selected through the Cochran formula by simple random sampling method. The research collection tool is a semi-structured interview and a researcher-made questionnaire. To analyze the data in the qualitative part, the data-based method was used; and in the quantitative part, SPSS and PLS software were used. The data were analyzed in the qualitative part by open, central, and selective coding; 111 open codes (concepts), 19 central codes (dimensions and components), and 6 selective codes (main categories) were counted. The findings of the qualitative section showed that the main and core categories in the form of six dimensions of causal conditions, central phenomenon, contextual conditions, intervening conditions, strategies, and consequences were upgraded to a higher abstract level and finally the research paradigm model was presented. In the quantitative section, the general management model was approved. Extended abstract Introduction Today, due to the fierce competition in the economy and the development of people's and organizations' awareness of finance and investment, capital markets have received more attention. On the other hand, some people are looking for the satisfaction of investors, and for this reason, they try to provide high quality products and services with low costs to the market. Based on this, performance review with emphasis on acceptable and diverse financial indicators as well as their classification based on priority can be of particular benefit to investors (Zolfaghari, 2015). Performance management is one of the most important topics emphasized by shareholders, managers and creditors; considering the development of capital markets, investors always want to know the success rate of managers in using their capital. Accordingly, financial ratios are the most important indicators that inform them about the company's financial status (Lin et al, 2020). One of the indicators of today's success is the existence of an efficient performance management system that continuously provides performance feedback to different levels of company management (Almatrooshi et al, 2016). With increasing competition in the field of production and services, organizations need to identify effective factors to improve their performance management (Liu et al, 2018). Performance management, in its new concept, is a cycle that helps managers, after setting goals and planning about the performance and behavior of employees under their supervision at the beginning of the evaluation period, to evaluate the amount and quality of program implementation and the achievement of goals at the end of evaluation period, and through rooting and analysis of satisfactory and unsatisfactory behaviors and performances and continuous application of this cycle, provide the basis for improving the performance and upgrading the behavior of employees (Abolalaei, 2010). Therefore, this research seeks to investigate the issue: what model can be designed for the general management of employees with an emphasis on performance management? Theoretical framework Employee performance management Performance management consists of two words: management and performance. Management has always been defined as doing work with others, promoting things through others, the process of planning, organizing, leading and controlling. Performance is also, in Mo'in Persian Glossory, synonymous with the result of work, amount of work, result or product. In the official definition of performance management, Daniels says: it is a practical data-oriented management system that consists of 3 main elements: measurement, feedback, and positive reinforcement. One of the common and constant demands of all managers is to improve the performance and continuous improvement of employees' behavior. When employees behave appropriately, and have desired and satisfactory performances: managers are also successful and run their organizations successfully. Performance management means measuring performance, but with the aim of simultaneously developing and improving employees and the organization in such a way that increasing the productivity of employees and work groups by acquiring skills and increasing their commitment and motivation leads to the development and growth of the organization (Khoshvaghti, 2016). The management style of martyr Haj Qassem Soleimani The first indicator of Haj Qassem Soleimani's management model is expertise. We have a duality called expertise and commitment. These are also complementary. There have been many debates. These are not opposites. It is even in quotes and hadiths. Expertise means professional knowledge and skill. Haj Qassem Soleimani was an expert in the field of military and security. In addition to being a scientist and at the same time, he was a skilled person in the field of security and military. He was even a professional diplomat. This is an important indicator. All managers of the country should have this. The second indicator is commitment. In our Islamic Republic, our emphasis is on heart and practical faith in the holy ideals of the system, governorship, and commitment to sacred religious laws. All these were perfectly present in Haj Qasim Soleimani. He never fell short of these ideals. He was a soldier of Islam. This means the peak of commitment. The third indicator is that he was tireless and hardworking. This should be of concern to managers. Farhadi et al, (2022) conducted a research under the title of the components of the management of the individual performance of the prevention police. Based on the research conducted for the management of individual performance, 6 components (self-evaluation, individual improvement, individual characteristics, individual spirituality, familiarity with expectations from employees, and professionalism), and 30 indicators were identified. Ahmadnejad (2022) conducted a research under the title of explaining the leadership model of martyr Qassem Soleimani. The result of the research showed that the model obtained from the analysis of the data is based on the personality traits of Martyr Soleimani as follows: Personality traits: faith in God, ethics, sacrifice and self-sacrifice, self-mastery. Functional characteristics: sociability, political man, expertise and commitment to work; which summarizes the results obtained about the basic themes. Research methodology The current research is applicable in terms of purpose, mixed in terms of implementation (qualitative-quantitative), and descriptive-survey in terms of nature. The participants in the qualitative part include 13 professors and experts in educational management and education managers, sampling by a targeted method, and the statistical population in the quantitative part includes 300 people from all the education and training staff of district one of Kerman, 187 of whom were selected through the Cochran formula by simple random sampling method. The research collection tool is a semi-structured interview and a researcher-made questionnaire. Research findings To analyze the data in the qualitative part, the data-based method was used; and in the quantitative part, SPSS and PLS software were used. The data were analyzed in the qualitative part by open, central, and selective coding; 111 open codes (concepts), 19 central codes (dimensions and components), and 6 selective codes (main categories) were counted. The findings of the qualitative section showed that the main and core categories in the form of six dimensions of causal conditions, central phenomenon, contextual conditions, intervening conditions, strategies, and consequences were upgraded to a higher abstract level and finally the research paradigm model was presented. In the quantitative section, the general management model was approved. Conclusion The current research was conducted with the aim of designing a general management model of employees with an emphasis on performance management. The results of this research is aligned with the results of Farhadi et al, (2022), Ahmadnejad (2022), Karimi Giglo (2021), Fuladi (2021), Udhayanan et al, (2021), Leviäkangas (2020), Liu et al, (2020), Mohammad Zaheri (2020), Yap et al, (2022), Alavian (2022), and Audenaert et al, (2021). Ghasemi (Ghasemi, 2022) confirmed the impact of performance management on job performance and job attachment at the individual level (Yap et al, 2022). The consequence of the existence of good performance management is loyalty and maximum use of employees' knowledge. According to the results of the research, the following suggestions are provided: